Sequence analysis of the GP5 protein of porcine reproductive and respiratory syndrome virus in Vietnam from 2007 to 2023 - Li, Gan; Li, Yilong; He, Cuihua; Liu, Xiyu; Lv, Chen; Liu, Kexin; Yu, Xingang; Zhao, Mengmeng (Frontiers in Microbiology, 2024)
Porcine reproductive and respiratory syndrome virus (PRRSV) is the causative agent of porcine reproductive and respiratory syndrome (PRRS), which is one of the most economically devastating viruses in the Vietnamese swine industry. In this study, with a view toward determining the genetic variation among PRRSV strains in Vietnam, we examined 271 PRRSV GP5 protein sequences obtained from strains isolated in Vietnam from 2007 to 2023, for which we constructed phylogenetic trees. Additionally, a collection of 52 PRRSV-1 strains and 80 PRRSV-2 strains isolated in different years were specifically selected for nucleotide and amino acid homology analysis and amino acid sequence alignment. The results revealed 76.1%-100.0% nucleotide and 75.2%-100.0% amino acid homologies for the PRRSV-1 GP5 gene, and 81.8%-100.0% nucleotide and 81.1%-100.0% amino acid homologies for the PRRSV-2 GP5 gene. Amino acid mutation sites in PRRSV-2 were found to be primarily distributed in the signal peptide region, antigenic sites, two T-cell antigen regions, two highly variable regions (HVRs), and in the vicinity of the neutralizing epitope, with a deletion mutation occurring in the neutralizing epitope, whereas amino acid mutations in the PRRSV-1 sequences were found to occur predominantly in two T-cell epitopes. Genetic analysis revealed that PRRSV-1 strains in Vietnam are of subtype 1 (Global), whereas PRRSV-2 strains are categorized into sublineages L1A, L5A, and L8E, with L8E being the predominantly prevalent strain at present. Recombination analyses indicated that no significant recombination events have occurred in any of the assessed 271 Vietnamese PRRSV strains. In summary, our analyses of 271 Vietnamese PRRSV strains have yielded valuable insights regarding the epidemiological trends and genetic dynamics of PRRSV in Vietnam, and will provide a theoretical basis for formulating prevention and control measures for PRRS and the development of PRRS vaccines.